PREVALENCE OF DEPRESSIVE SYMPTOMS, ANXIETY, SUICIDAL IDEATION AND ASSOCIATED FACTORS AMONG HIGHER EDUCATION STUDENTS - Carmen de Aquino Nunes, Jenyfer; Oliveira Lima Magalhães, Daniela; Vitória Silva Rodrigues, Anne; Nami Utsunomya Saraiva, Arissa; Carlos Pereira de Jesus, Ely; Karine de Oliveira Santos, Evaine; Fagundes Souto, Daniella; Fonseca Lisboa, Bernardo; Almeida Nunes, Tatiana; Azevedo Ledo, Lucas; Abrahão Neto, Alexi; Barbosa Rocha, Diego; et al. (Health and Society, 2024)
Objective: To estimate the prevalence of depressive symptoms, anxiety and suicidal ideation and associated factors among higher education students. Methods: an integrative literature review was conducted. Articles retrieved from the secondary databases Virtual Health Library (VHL), Latin American and Caribbean Health Sciences Literature (LILACS), the Scientific Electronic Library Online (Scielo), the Online System for Search and Analysis of Medical Literature (MEDLINE), the National Library of Medicine (Pubmed) and the Scopus database were analyzed using the following descriptors: depression, anxiety, suicidal ideation, and students. Studies published in Portuguese, English, Spanish and that dealt directly with the subject of study were considered. Results: previous health conditions, sociodemographic and social variables, family and interpersonal relationships, and specific aspects of the undergraduate course and the institution related the prevalence of depressive symptoms, anxiety, and suicidal ideation. Conclusion: a significant prevalence of depressive symptoms, anxiety and suicidal ideation was identified, the variables associated with the outcomes analyzed are heterogeneous and identifies the need for a systematic and multifactorial action to reduce cases and satisfactorily meet demands.